PENAPISAN BAKTERI TERMOFILIK PENGHASIL AMILASE DARI SUMBER AIR PANAS DONDANG DI KECAMATAN MUARA JAWA - Muhammad Taufik A. A. R; Winni Astuti; Erwin Erwin (PROSIDING SEMINAR KIMIA, 2017)
Amylase producing bacteria have been isolated from Dondang hot springs in Muara Jawa sub-district based on clear zone. Dondang hot springs became the site of the discovery of thermostable bacteria. Obtained 1 selected isolate showed amylase activity with the formation of clear zone around the colony on solid media containing 1% starch. Based on the morphology and physiology tests the selected isolates showed the genus Bacillus sp. The results showed total protein concentration of crude extract of enzyme from amylase producing bacteria isolate that is 2, 4068 μg /mL. Keywords: Thermophilic bacteria, amylase, clear zone, protein concentration.